The Cellular Functions and Molecular Mechanisms of G-Quadruplex Unwinding Helicases in Humans - Liu, Yang; Zhu, Xinting; Wang, Kejia; Zhang, Bo; Qiu, Shuyi (Frontiers in Molecular Biosciences, 2021)
G-quadruplexes (G4s) are stable non-canonical secondary structures formed by G-rich DNA or RNA sequences. They play various regulatory roles in many biological processes. It is commonly agreed that G4 unwinding helicases play key roles in G4 metabolism and function, and these processes are closely related to physiological and pathological processes. In recent years, more and more functional and mechanistic details of G4 helicases have been discovered; therefore, it is necessary to carefully sort out the current research efforts. Here, we provide a systematic summary of G4 unwinding helicases from the perspective of functions and molecular mechanisms. First, we provide a general introduction about helicases and G4s. Next, we comprehensively summarize G4 unfolding helicases in humans and their proposed cellular functions. Then, we review their study methods and molecular mechanisms. Finally, we share our perspective on further prospects. We believe this review will provide opportunities for researchers to reach the frontiers in the functions and molecular mechanisms of human G4 unwinding helicases.